2013
DOI: 10.1097/coc.0b013e31823fe639
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal Template-guided Mapping Biopsy as a Staging Procedure to Select Patients Best Suited for Active Surveillance

Abstract: TRUS biopsy underestimates disease extent and Gleason score in some patients. TTMB provides a more accurate assessment of the presence of aggressive histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…The confirmatory biopsy is an essential tool as reports have shown that more than a third of patients treated with AS for PCa are upgraded at the time of repeat biopsy or radical prostatectomy. 7,11,12 In our study TP-24 biopsy resulted in estimated upgrading prevalence similar to that of TP-V biopsy, although formal equivalence testing in a much larger cohort would be necessary to formally rule out a meaningful difference.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The confirmatory biopsy is an essential tool as reports have shown that more than a third of patients treated with AS for PCa are upgraded at the time of repeat biopsy or radical prostatectomy. 7,11,12 In our study TP-24 biopsy resulted in estimated upgrading prevalence similar to that of TP-V biopsy, although formal equivalence testing in a much larger cohort would be necessary to formally rule out a meaningful difference.…”
Section: Discussionsupporting
confidence: 63%
“…7e9 By systematically sampling the entire prostate TP BX provides a more accurate representation of the true extent of disease compared to a standard 12-core transrectal ultrasound biopsy in men considering AS. 7 However, to our knowledge the optimal TP BX technique has not been elucidated.…”
mentioning
confidence: 98%
“…This is a percutaneous approach, in which the biopsy needle pierces through the perineum parallel to the urethra, allowing for improved sampling of the anterior and apical prostate regions while decreasing the risk of sepsis and urethral damage [1921]. Transperineal biopsy results have also been shown to improve cancer detection rates, reduce the risk of underestimating tumor grade, and decrease the false-negative results compared to TRUS-guided biopsies [22, 23]. Targeted in-bore biopsies allow for clear needle visualization during biopsy and most importantly, confirm with imaging the correct location of the needle in the suspicious lesion, thus improving accuracy and reducing the number of core biopsies needed [11, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Using such a volume-adjusted stringent systematic saturation approach, the combination of the two biopsy methods did not have significant additional benefit. The detected overall cancer rates with 65% for all patients and 72, 45, and 81% for the primary biopsy cohort, the repeat biopsy cohort, and the surveillance cohort, respectively, are clearly compatible compared to other transperineal template-guided saturation (TTSB) or mapping biopsy studies (TTPM): for primary biopsy cohorts, detection rates of 54-76% have been reported using a mean amount of 19-54 cores [20][21][22][23] ; and for repeat biopsy cohorts, detection rates of 26-68% with a mean amount of 18-59 cores have been reported [21,22,[24][25][26][27][28][29] . In series in which TTPM biopsies was followed by RP, TTPM was highly accurate in detecting and excluding clinically significant disease [30,31] .…”
Section: Discussionmentioning
confidence: 74%